Picture-based crop insurance: A randomized controlled trial evaluating the impacts of using smartphone camera data for claims verification in India - Ceballos, Francisco; Gaur, Pushkar; Gupta, Monali; Kannan, Samyuktha; Kramer, Berber (International Initiative for Impact Evaluation, 2025)
Exposure to weather hazards, pests, crop diseases, and climate change threaten the livelihoods of many smallholder farmers in low- and middle-income countries. A lack of agricultural insurance has severe financial consequences for farmers in the aftermath of shocks; however, even in uneventful years, it discourages risk-averse farmers from investing in profitable agricultural production opportunities, thereby limiting the adoption of practices and technologies that would improve productivity and income. As a result, many countries are focusing on agricultural insurance as a means of reducing farmers’ exposure to production risks and increasing investments. This report describes findings from an impact evaluation of a novel crop insurance scheme in the state of Haryana, India.